CD19 Deficient B Cell Abnormality and Selective IgM Deficiency in a Malay Child. A Case Report. - Nohl, L.M.; Rus Anidah, R.A.; Thiyagara, N.; Abd Hamid, Intan Juliana; Hashim, I.; Latif, A.H. (Springer Verlag, 2012)
Cases of CD 19 deficiency from South East Asia has rarely been reported. A, 1l yr Malay boy was referred with recurrent infections with 2 episodes of'chickenpox at age 2 years. He had repeated episodes of pneumoniae and bronchiectasis by age 6 years. Physical examination revealed gross clubbing with crepitations at both lung bases. IV lg administration was instituted with clinical improvementlaboratory data: Serum Ig (g/l )IgG 8.37[n 4.95- 16.56 ], IgA 0.92[n 0.30-2.35 7, lgM 0.21 [0.32-1.4}]Lymphocyte subset (age 1l) CD19 Q o , CD20 11.26% (12-22)CD3 83.64% (n 66-76) ,CD4 36.25 ( 33-41),CD8 41.55 (27- 35), CDl6+56 I1.6 %. (9-16),Specific antibody response to polysaccharide antigen was impaired ; whileNBT , lymphocyte proliferation to (PHA ) were normal, Btk protein 18% (control 87.8 %). Our finding conforms with a diagnosis of CD19 deficiency with selective IgM deficiency and partial defective Btk protein expression.